Modeling cell-mediated immunity in human type 1 diabetes by engineering autoreactive CD8+ T cells - Peters, Leeana D.; Yeh, Wen-I; Arnoletti, Juan M.; Brown, Matthew E.; Posgai, Amanda L.; Mathews, Clayton E.; Brusko, Todd M. (Frontiers in Immunology, 2023)
The autoimmune pathogenesis of type 1 diabetes (T1D) involves cellular infiltration from innate and adaptive immune subsets into the islets of Langerhans within the pancreas; however, the direct cytotoxic killing of insulin-producing β-cells is thought to be mediated primarily by antigen-specific CD8+ T cells. Despite this direct pathogenic role, key aspects of their receptor specificity and function remain uncharacterized, in part, due to their low precursor frequency in peripheral blood. The concept of engineering human T cell specificity, using T cell receptor (TCR) and chimeric antigen receptor (CAR)-based approaches, has been demonstrated to improve adoptive cell therapies for cancer, but has yet to be extensively employed for modeling and treating autoimmunity. To address this limitation, we sought to combine targeted genome editing of the endogenous TCRα chain gene (TRAC) via CRISPR/Cas9 in combination with lentiviral vector (LV)-mediated TCR gene transfer into primary human CD8+ T cells. We observed that TRAC KO of the endogenous TCRα enhanced de novo TCR pairing, which permitted increased peptide:MHC-dextramer staining. Moreover, TRAC KO and TCR gene transfer increased markers of activation and effector function following activation, including granzyme B and interferon-γ production. Importantly, we observed increased cytotoxicity toward an HLA-A*02:01 human β-cell line by HLA-A* 02:01 restricted CD8+ T cells engineered to recognize islet-specific glucose-6-phosphatase catalytic subunit (IGRP). These data support the notion of altering the specificity of primary human T cells for mechanistic analyses of autoreactive antigen-specific CD8+ T cells and are expected to facilitate downstream cellular therapeutics to achieve tolerance induction through the generation of antigen-specific regulatory T cells.